COVID-19 and Dengue: A potentially emerging healthcare challenge for Pakistan (Journal of Fatima Jinnah Medical University, 2021)
Pakistan is facing the third wave of the SARS-CoV-2 pandemic and could head towards the fourth one. Although the burden of COVID-19 remained significantly low in the country as compared to its neighboring countries despite similar gene pool, health system, and climatic conditions, still Pakistan has dealt with the disease with relative effectiveness. The pandemic imposed immense pressure on the public health systems due to increased demand for specialized isolation wards and intensive care units and disease-related morbidity and mortality. Many of the tertiary care hospitals in the major pandemic-stricken districts have been transformed into specialized centers dedicated to the treatment of COVID-19. This resulted in diverting major hospital resources and manpower to deal with the pandemic at the cost of other medical and surgical conditions. A recent pulse survey conducted by World Health Organization (WHO) in 135 countries demonstrated that the SARS-CoV-2 pandemic severely affected the global health services, while services for endemic tropical diseases (like dengue) were affected in 44% of countries, especially in resource-limited countries. Moreover, large-scale community-based interventions including vector surveillance and control were disrupted in 60% of the countries.1 Another survey by WHO on malaria control in sub-Saharan Africa demonstrated a >20% increase in malaria cases and a doubling of malaria-associated deaths due to a decline in malaria control activities during the pandemic. It is expected that the future catastrophe due to malaria might be much greater than the COVID-19 in endemic regions. Therefore, WHO recommends continuous monitoring, surveillance, and treatment to control the spread of malaria.2
Keywords: Dengue; COVID-19; Epidemic